A Cross-Cultural Comparison of Local and Foreign Tourist Preferences Towards Selected Visual Images of Malaysian Landscapes - Talib, Hamimah (2005)
Image has been supported as one of the primary factors in deciding where to travel. The great stride in tourism industry has brought up the interest in investigating what people like in the environment. This study compares the preferences for visual images of Malaysian landscapes among the local and foreign tourists in Malaysia. There were 120 local and 74 foreign tourists sampled in this study. The settings consisted of 60 colour photographs of four categories: beach, highland, rural, and landmark structure. Two phases were involved in the study. In the first phase, Category-Identifling Methodology (CIM) (Kaplans,1989) was used to measure people's reaction to landscapes, where participants were exposed to the set of 60 colour photographs. The participants rated each of the scene on a seven-point rating scale, for their preference and reasons for their preference were recorded. The second phase involved a focus group of selected panels fiom different fields to get their opinions on the content of the preferred images and the economic values in terms of their willingness to pay for the images. This study has identified significant differences in the preferences of local and foreign tourists for highland and beach category. Comparison of preference shows that the local tourists prefer landscape images with "dense, green vegetation with fav elements; prospect and refige" characteristics; the British and Japanese both prefer the "Isolated, unpolluted, beach and sea; coastal forest" landscape images and the Chinese prefers images with "skyline, tall buildings, and greens, blue sky or water and white clouds; modem architecture ". A Content Analysis for reasons of preferences reveals that images with more 'natural', 'peacefir, 'beauti$d', 'colourjiil' and the presence of 'water' elements are more preferred. Willingness To Pay (WTP) analysis finds that a single one time donation that was agreed upon by the panellists to preserve the landscape resources is RM466.67 (mean), while the maximum amount per year that they are willing to pay to enjoy the resources is RM3 14.44 (mean).